Analisis Media Monitoring terhadap BPJS Kesehatan di Tengah Lonjakan Kasus DBD di Indonesia pada Februari-Maret 2024 - Marva Razita Ramelan (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
In early 2024, deaths from Dengue Hemorrhagic Fever (DHF) increased again in Indonesia, with the number of cases higher than the previous year. This condition raises concerns because DHF remains a serious public health problem. The World Health Organization (WHO) emphasized that the key to reducing mortality lies not only in early detection but also in public access to fast, effective, and equitable health services. This statement aligns with the second point in the document "National Dengue Control Strategy 2021–2025" issued by the Ministry of Health, in which the government is committed to strengthening health security. In efforts to ensure this strengthening, public participation plays a crucial role, particularly through the public oversight function channeled through the media. The media acts as a bridge of information and a tool of social control over government performance, including in monitoring the provision of health services by BPJS Kesehatan. This study aims to analyze how news about health security reaches the public, using Brand24 media monitoring as an analytical tool. The research method used was descriptive qualitative, focusing on mapping issues, sentiments, and narratives developing in the digital space. The analysis showed that news containing the keyword "BPJS Kesehatan" was dominated by positive news, with several minor topics discussing aspects of public service. This finding indicates a media tendency to project a positive image of the institution, although further study is needed regarding media bias in the context of health security reporting in Indonesia. Future research is expected to explore the relationship between media framing, public interest, and the effectiveness of national health programs.